ANALYZING TRANSFER PROBLEMS IN SECOND LANGUAGE ACQUISITION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
All people have interference phenomena (negative influence of the first language on the second) and transfer (positive transfer of skills from one language to another). The article identifies language interference that appears while learning several foreign languages, in addition it explores transfer problems in second language acquisition.